Indicadores de sustentabilidade fiscal do Ceará: análise e projeções para 2015-2023 - Gomes Júnior, José Roberto Severiano (2024)
This study analyzes the sustainability of the public debt of the State of Ceará for the period 2015 to 2023, using the indicators proposed by Blanchard (1990). Two indicators were analyzed: fiscal sustainability () and fiscal gap (), based on data obtained from the Summary Reports on Budget Execution (RREO) available on Siconfi, and from sources at IBGE and IPECE. The results showed that, for most of the period analyzed, the τIS indicator was negative, suggesting fiscal sustainability of Ceará's public accounts. However, the years 2018, 2022, and 2023 presented positive values, indicating the need for fiscal adjustments. The second indicator, , demonstrated that the fiscal sustainability of Ceará depends significantly on the spending policies adopted. In scenarios where spending increases, the need for higher taxation to maintain sustainable debt becomes evident. Conversely, reducing expenditures improves fiscal sustainability, as reflected in the negative τIG values. From 2021 onwards, there was a deterioration in fiscal sustainability, attributed to increased public spending, especially in response to the COVID-19 pandemic, and the high interest rates imposed by the Central Bank of Brazil. Previous studies corroborate these findings, highlighting the fiscal challenges faced by the state. It is concluded that, although Ceará has presented a predominantly sustainable fiscal trajectory, specific periods require attention and fiscal adjustments to ensure the continuity of public finance sustainability. Effective debt management and stringent expenditure control are essential to avoid escalating interest costs and ensure long-term financial stability.